THE FUTURE OF REGIONAL LEADERSHIP AND TURKEY'S POSITION COMPARED TO THE MIDDLE EASTERN UNDERGRADUATE STUDENTS - (:unkn) unknown (MARMARA UNIV, 2018)
This research is a quantitative survey to determine the value of the perceptions of the cause of the chaos in the Middle East is the fact that the western people have broken up the Ottoman State and we Turks can provide peace, security in the region in the Middle East and the viewpoint of the Middle East towards our country. In this context, in order to collect data, while conducting a survey for university students from Middle East countries who come to Turkey to study on undergraduate and graduate degrees, also a literature scanning for ever-changing Turkish foreign policy in the 21st century and regional moves have been made. According to the findings, Middle Eastern students are regarding Turkey, Iran and Saudi Arabia in the forefront as a regional leader. It has been observed that most of the students who have seen Iran and Saudi Arabia as leaders, have argued that the regional leader should be Turkey.
Keywords: Middle East; Turkey; Leadership; Foreign Policy